1989
DOI: 10.1002/1097-0142(19890201)63:3<428::aid-cncr2820630305>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Continuation of chemotherapy versus supportive care alone in patients with inoperable non-small cell lung cancer and stable disease after two or three cycles of MACC. Results of a randomized prospective study

Abstract: Recommendations concerning the continuation of chemotherapy in nonresponding patients with non-small cell lung cancer (NSCLC) and stable disease after the first chemotherapy test are empirical and often conflicting. Between 1984 and 1987, 116 inoperable NSCLC patients were treated with methotrexate, doxorubicin, cyclophosphamide, and lomustine (MACC regimen). After two or three cycles of therapy, 74 patients were judged to have stable disease and assigned at random either to chemotherapy maintenance with the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…However, prior studies in NSCLC have failed to show convincing clinical benefit as measured by overall survival advantage in patients treated with a prolonged course of chemotherapy (14)(15)(16)(17). Some of these initial studies were fraught with methodological flaws that either led to study redesign or post hoc adjustment of the power of the study to detect the anticipated survival differences (14).…”
Section: Maintenance Therapy: the Pastmentioning
confidence: 99%
See 2 more Smart Citations
“…However, prior studies in NSCLC have failed to show convincing clinical benefit as measured by overall survival advantage in patients treated with a prolonged course of chemotherapy (14)(15)(16)(17). Some of these initial studies were fraught with methodological flaws that either led to study redesign or post hoc adjustment of the power of the study to detect the anticipated survival differences (14).…”
Section: Maintenance Therapy: the Pastmentioning
confidence: 99%
“…However, prior studies in NSCLC have failed to show convincing clinical benefit as measured by overall survival advantage in patients treated with a prolonged course of chemotherapy (14)(15)(16)(17). Some of these initial studies were fraught with methodological flaws that either led to study redesign or post hoc adjustment of the power of the study to detect the anticipated survival differences (14). Of greater significance is the fact that some of the trials employed chemotherapy regimens that, in light of contemporary practice, will be considered too toxic for maintenance or prolonged therapy (14,15,17).…”
Section: Maintenance Therapy: the Pastmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1997, a consensus statement by American Society of Clinical Oncology recommended that chemotherapy in advanced stage NSCLC should not be extended beyond eight cycles [6]. These recommendations were based on the only trial completed at that time by Buccheri et al which compared non-platinum based chemotherapy after 2-3 cycles to continuous treatment [7]. No survival benefit was seen in continuous treatment.…”
Section: Duration Of First Line Chemotherapy In Nsclcmentioning
confidence: 99%
“…Several trials showed no signifi cant diff erences in survival or quality of life (QoL) between patients undergoing a short or long-duration of combination chemotherapy [4,[9][10][11][12]. Th ese studies demonstrate that continuation of combination chemotherapy beyond a defi ned number of cycles did not provide additional benefi t, but it was associated with higher, clinically relevant toxicities.…”
Section: Combination Chemotherapymentioning
confidence: 99%